Can explaining less be more? Enhancing vocabulary through explicit versus elaborative storytelling. Issue 2 (April 2018) - Vaahtoranta, Enni; Suggate, Sebastian; Jachmann, Cornelia; Lenhart, Jan; Lenhard, Wolfgang
Shared reading represents an established practice to foster preschool vocabulary development, particularly when coupled with explicit instruction in word meanings. However, a question remains as to whether explicit word definitions detract from story delivery and hence language learning. Accordingly, this study compared explicit versus story-focused, elaborative storytelling in a 2 × 2 pre–posttest randomized and counterbalanced mixed design with 63 preschoolers. Children were told two fairytales daily across three sessions in either explicit or elaborative conditions, whereby target words were accompanied with either an explicit (e.g., definition, question) or elaborative (e.g., gesture, metaphor, rhetorical question) word learning technique. Stories were either read aloud or freely told by experimenters. Both conditions resulted in similarly large gains in target vocabulary and performance on a story retelling. Some differential effects were found, with there being a larger difference between explained versus incidental words in the explicit condition. Furthermore, children in the elaborative condition were less restless during storytelling. The findings suggest that both elaborative as well as explicit approaches promote vocabulary growth and provide some evidence of differential effects for child behavior during storytelling.